MADRASAH DAN TRANSMISI ILMU PENGETAHUAN DALAM PERADABAN ISLAM - Dewi, Rusmala (Nurani, 2014)
Abstract: Education is a milestone in the progress of civilization; a nation would be stronger if the education is well managed. Vice versa, the decline or collapse of a nation will be started if the management of the nation's education was not good. Islamic civilization setback daulah Abbasid era in Baghdad, one of the Reasons was the destruction of educational centers that carry the development of science.ملخص: التعليم هو حجر الزاوية في تقدم الحضارة. فإن الأمة تكون أقوى إذا تمكنت التعليم أيضا. بالعكس، ومن المقرر بدء تراجع أو انهيار للأمة إذا كانت إدارة التعليم في البلاد ليست جيدة. نكسة الحضارة الإسلامية دوالها العصر العباسي في بغداد، كان واحدا من أسباب تدمير المراكز التعليمية التي تحمل تطور العلم.Kata Kunci: madrasah, peradaban islam